Manajemen Perpustakaan Sekolah (Studi pada Perpustakaan Ceria SMA N 1 Rejang Lebong) - Rhoni Rodin; Diah Arum Retnowati; Yanti Putri Sasmita (THE LIGHT : Journal of Librarianship and Information Science, 2021)
School library management is basically a process of optimizing human, material, and budgetary contributions to achieve library goals. The purpose of this study is to describe the management of the Ceria library at SMA N 1 Rejang Lebong, the specific purpose of which is to find out how the implementation of the management function in the cheerful library at SMA N 1 Rejang Lebong starts from planning, organizing, implementing (actuating), controlling which is applied in the cheerful library of SMA N 1 Rejang Lebong. This research method the author uses a descriptive research method with a qualitative approach to find out how the implementation of library management in the cheerful library of SMA N 1 Rejang Lebong. The subject of this research is the head of the library, librarians, teachers, students and schools. The results of this study are the implementation of management functions in the cheerful library of SMA N 1 Rejang Lebong has been implemented well.